Ancestors, kings, and the Dao - Cook, Constance A. (Published by the Harvard University Asia Center, 2017)
""Ancestors, Kings, and the Dao outlines the evolution of musical performance in early China, first within and then ultimately away from the socio-religious context of ancestor worship. Examining newly discovered bamboo texts from the Warring States period, Constance A. Cook compares the rhetoric of Western Zhou (1046-771 BCE) and Spring and Autumn (770-481 BCE) bronze inscriptions with later occurrences of similar terms in which ritual music began to b
Keywords: Ancestor worship -- China -- History -- To 1500.; Eulogies -- China -- History -- To 1500.; Laudatory poetry.; Taoism and the arts -- China -- History -- To 1500.; China -- History -- Zhou dynasty, 1122-221 B.C.; China -- History -- Warring States, 403-221 B.C.; Poésie élogieuse.; Chine -- Histoire -- 1122-221 av. J.-C. (Dynastie des Zhou); Chine -- Histoire -- 403-221 av. J.-C. (Royaumes combattants); Ancestor worship; Eulogies; Laudatory poetry; Taoism and the arts; Zhou Dynasty (China); China; To 1500; History